The Influence of Work Motivation, Compensation and Organizational Culture On Organizational Commitment Through Job Satisfaction As A Mediating Variable - Santi Suciningtyas; Delaga Nurwisda; Susidin Susidin (Return : Study of Management, Economic and Bussines, 2022)
Background: Public perception of public services is still influenced by the lack of organizational commitment of government officials. Aim: this research is to analyze the mediating relationship between Work Motivation, Compensation and Organizational Culture through Job Satisfaction and Organizational Commitment Performance: a study of employees in public service agencies. The objective of this research subject is Civil Servant at Disperindagkop Pemalang Regency. The population in this study is 96 employees. Method: This study uses explanatory research for causal relationships between variables through hypothesis testing.sampling techniques with purposive sampling, The data analysis methods used are path analysis and Sobel tests to test indirect influences (mediation effects). Findings: Based on the results of data analysis, several things were concluded, including: there is a significant direct effect of Work Motivation, Compensation and Organizational Culture on Organizational Commitment through Job Satisfaction as a mediating variable. In addition, Job Satisfaction also has a significant effect on employee Organizational Commitment. ly acsept and use application technology to develop their business.